Genome-Wide Identification of Peanut KCS Genes Reveals That AhKCS1 and AhKCS28 Are Involved in Regulating VLCFA Contents in Seeds - Huai, Dongxin; Xue, Xiaomeng; Li, Yang; Wang, Peng; Li, Jianguo; Yan, Liying; Chen, Yuning; Wang, Xin; Liu, Nian; Kang, Yanping; Wang, Zhihui; Huang, Yi; et al. (Frontiers in Plant Science, 2020)
The peanut (Arachis hypogaea L.) is an important oilseed crop worldwide. Compared to other common edible vegetable oils, peanut oil contains a higher content of saturated fatty acids (SFAs), approximately 20–40% of which are very long chain fatty acids (VLCFAs). To understand the basis for this oil profile, we interrogated genes for peanut β-ketoacyl-CoA synthase (KCS), which is known to be a key enzyme in VLCFA biosynthesis. A total of 30 AhKCS genes were identified in the assembled genome of the peanut. Based on transcriptome data, nine AhKCS genes with high expression levels in developing seeds were cloned and expressed in yeast. All these AhKCSs could produce VLCFAs but result in different profiles, indicating that the AhKCSs catalyzed fatty acid elongation with different substrate specificities. Expression level analysis of these nine AhKCS genes was performed in developing seeds from six peanut germplasm lines with different VLCFA contents. Among these genes, the expression levels of AhKCS1 or AhKCS28 were, 4–10-fold higher than that of any other AhKCS. However, only the expression levels of AhKCS1 and AhKCS28 were significantly and positively correlated with the VLCFA content, suggesting that AhKCS1 and AhKCS28 were involved in the regulation of VLCFA content in the peanut seed. Further subcellular localization analysis indicated that AhKCS1 and AhKCS28 were located at the endoplasmic reticulum (ER). Overexpression of AhKCS1 or AhKCS28 in Arabidopsis increased the contents of VLCFAs in the seed, especially for very long chain saturated fatty acids (VLCSFAs). Taken together, this study suggests that AhKCS1 and AhKCS28 could be key genes in regulating VLCFA biosynthesis in the seed, which could be applied to improve the health-promoting and nutritional qualities of the peanut.